A case series of prenatal hepatic hilar cyst in the presence of a gallbladder - navigating the dilemma between biliary atresia and choledochal cyst - Ana M. Calinescu; Anne-Laure Rougemont; Valérie A. McLin; Nathalie M. Rock; Céline Habre; Barbara E. Wildhaber (BMC, 2024)
Abstract Background Prenatally diagnosed hepatic hilar cysts are a challenging finding for the clinician. They can either be a sign of cystic biliary atresia (BA) or a choledochal cyst (CC), two diagnoses with different postnatal management and prognosis. Based on a case report of four patients, we aim to propose a management algorithm for prenatally diagnosed "hepatic hilar cysts". Case presentation A hepatic hilar cyst, ranging from 5 to 25 mm, was detected prenatally in all four girls confirmed postnatally along with the presence of a gallbladder. Stool color was normal until two weeks of life at which time the stool color became lighter, and the patients developed cholestasis. All were operated before seven weeks of life: Case 1 had a CC with patent but irregular intrahepatic bile ducts at intraoperative cholangiogram, and no communication with the duodenum. A Roux-en-Y bilioenteric anastomosis was performed. The cyst showed complete epithelial lining loss, and liver pathology showed BA features. Case 2 had the final diagnosis of cystic BA with patent but abnormal intrahepatic bile ducts. She underwent two operations: the first operation at four weeks as described for case 1, since intraoperative findings were similar, as was histology. As cholestasis increased postoperatively, she underwent a Kasai hepato-porto-enterostomy six weeks later, where distinct BA findings were found with complete scarring of the hilar plate. Case 3 had a cystic BA with the cyst located within the common bile duct and atretic bile ducts proximal to the porta hepatis. It exhibited no communication with the liver or duodenum. A Kasai operation was performed, with histology showing complete epithelial loss within the cyst wall and scarring of the hilar plate. Case 4 had a cystic BA presenting a completely obliterated hepatic duct with the cyst lying within the common bile duct. A Kasai procedure was performed. Histology showed a common bile duct with a residual lumen of 0.1 mm. Conclusions The spectrum of disease from CC to BA in the setting of a prenatally discovered hepatic hilar cyst is emphasized. Even if cholangiogram differentiates most patients with BA from those with CC, caution is advised for transitional types.